Teaching Fellowship : Benchmarking Partnerships for Graduate Employability : Final Report. - Oliver, Beverley (Australian Learning and Teaching Council (ALTC), 2010)
Final report of a Teaching Fellowship at Curtin University. This fellowship aimed to encourage course leaders from universities across Australia to engage in benchmarking partnerships with a focus on graduate employability, and to disseminate curriculum tools which would enable that focus: a curriculum mapping tool; graduate and employer surveys; and a needs analysis which assembled course quality indicators. During the fellowship journey, the original aims developed into a more comprehensive approach presented within a framework.